FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERAN KADER KESEHATAN DALAM PELAKSANAAN PHBS DI KELURAHAN SARIREJO KOTA SEMARANG - Millati Azka Safitri; Priyadi Nugraha P.; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
PHBS is an aware health-based behavior that is done by family members to help themshelves regarding to their health and to play active roles in helath-based activities in their surrounding. The percentage of PHBS in Sarirejo Village is one the worst PHBS among 117 villages, and decreases 1.02%. In 2016 was 51%, from 52.02% in 2015. The roles of health cadres in promoting PHBS are expected to relate with the implementation of PHBS in Sarirejo Village, Semarang. The purpose of this study was to determine the factors related to the roles of health cadres in the implementation of PHBS.This study was an analytical descriptive research with quantitative approach. There are 49 people as population. Samples were 33 people health cadres that chosen using simple random sampling. The data was analysed using statistical Fisher’s Exact Test with significance level of 5%. The results of this study showed that 84.8% of health cadres perform their roles well. The variable that was related with the roles of health cadres is the attitudes toward PHBS and the roles of cadres (p = 0.021). Meanwhile the variables that were not related with the roles of health cadres are age, latest education, job, knowledge of PHBS, knowledge of the roles of cadres, the availability of facilities, the availability of cost, skills, the support of the municipality, and the support of community health centers.The leader of health cadre as key person need to motivate her members so that they can keep good attitude towards health cadre’s roles. Especially at desease recording and approaching to public figures.